Illuminating the process: Enhancing the impact of continuing professional education on practice. (February 2015) - Clark, Elisabeth; Draper, Jan; Rogers, Jill
Summary: Background: There has been significant global investment in continuing professional education (CPE) to ensure healthcare professionals have the knowledge and skills to respond effectively to the needs of patients/service users. However, there is little evidence to demonstrate that this investment has had a tangible impact on practice. Furthermore, the current emphasis on evaluating outcomes has overlooked the importance of underlying processes which, when positive, are essential to good outcomes. Objective: The aim of this study was to identify the processes that key stakeholders perceive to be most important in facilitating a positive impact of CPE on practice. Design/method: A qualitative design using two rounds of semi-structured interviews which were recorded and transcribed prior to analysis, informed by template analysis techniques. Setting: Two acute trusts, one primary care trust and two higher education institutions in one geographical region in England. Participants: Representatives from four stakeholder groups—students, managers, educators and members of each healthcare organisation's governing board. A total of 35 interviews were conducted in the first round and 31 interviews in the second round ( n = 66). Results: Four overarching themes were identified that illuminate stakeholders' perspectives of the important factors affecting the process of CPE: organisational structure, partnership working, a supportive learning environment and changing practice. Conclusions: This study suggests that a positive organisational culture, effective partnership working between key stakeholders with an understanding of each other's perspectives, aspirations and constraints, and a supportive learning environment in both the practice setting and education environment are central to establishing a culture and context where CPE can thrive and exert a positive influence on improving patient/service user experience and care. It is argued that an understanding of the processes that facilitate effective CPE is a crucial first step before it is possible to meaningfully evaluate outcomes.